Interfaces of educational policies on scientific production and training of researchers in Latin America - Consaltér, Evandro; Fávero, Altair Alberto (Universidade Estadual de Campinas, 2019)
This text is a review of the book “Production of Scientific Knowledge and Researcher Training in Latin America: the investigation of educational policies in check”, published by Mercado de Letras, December 2017. The collection is organized by Professor Maria de Lourdes Pinto de Almeida and is the result of a research project developed from 2014 to 2016 by researchers from the Iberoamerican Network for Studies and Research in Higher Education Policies and Processes - RIEPPES. Headquartered in the Graduate Program in Education of the University of Western Santa Catarina - UNOESC, the Network is also linked to the International Group for Studies and Research in Higher Education - GIEPES, based in the State University of Campinas - Unicamp. The work in question brings together texts from researchers from Brazil, Chile, Mexico and Spain. The collection offers a rich and important contribution to the discussion of the directions of researcher education policies and the production of knowledge in the area of ​​educational policies.